Re-engineering fiber optic production process by simulation, design for assembly line - Wichai Chattinnawat (2018)
This research aims to re-engineer the process in order to improve both productivity and quality of LC Duplex connector optical fiber production line. This re-engineering process research for fiber optic production process had adopted line balancing, design of assembly line and cellular manufacturing to improve the productivity and quality of the process. Simulation had been used as a mechanism for finding solutions of improvement. The design for assembly line adopts the optimization algorithm of minimizing the maximum between the operation times of each cells and its average. The results showed that the productivity was increased, line balancing efficiency was dramatically improved, and work in-process was reduced as well as the improvement in quality. © 2008 IEEE.